DGUOK-AS1 acts as a tumorpromoter through regulatingmiR-204-5p/IL-11 axis in breast cancer - Yiran Liang; Fangzhou Ye; Yajie Wang; Yalun Li; Yaming Li; Xiaojin Song; Dan Luo; Li Long; Dianwen Han; Ying Liu; Zekun Wang; Bing Chen; et al. (Elsevier, 2021)
Breast cancer is one of the most lethal malignancies among women; however, the underlying molecular mechanism involved in the progression and metastasis of breast cancer remains unclear. Numerous studies have confirmed that long noncoding RNAs are abnormally expressed in breast cancer and play crucial roles in cell proliferation and metastasis. In the study, we evaluated the functional role and detailed mechanism of DGUOK-AS1 in breast cancer progression and metastasis. DGUOK-AS1 knockdown suppressed proliferation, migration, and invasion of breast cancer cells in vitro and in vivo. Mechanistically, miR-204-5p was identified as an inhibitory target of DGUOK-AS1, which served as a tumor suppressor in breast cancer. Significantly, we found that the ectopic expression of miR-204-5p could counteract DGUOK-AS1-mediated promotion of cell proliferation and metastasis in breast cancer. Moreover, IL-11 was found to be the downstream target of miR-204-5p, and DGUOK-AS1 could protect IL-11 from miR-204-5p-mediated degradation. DGUOK-AS1 overexpression promoted breast cancer cell migration, angiogenesis, and macrophage migration, mediating by the increased secretion of IL-11, which was extremely important for cancer progression. Collectively, our studies reveal that DGUOK-AS1/miR-204-5p/IL-11 axis plays a significant role in the progression and metastasis of breast cancer, and DGUOK-AS1 might be a novel biomarker and therapeutic target for breast cancer.